A Two-Stage Multi-Objective Allocation Model for Students’ Admission into Academic Departments in A Malaysian Public University - Hassan, Nasruddin (2007)
We develop, formulate, verify and later validate a multiobjective model of student admission. Through a two-stage optimization procedure the model seeks to maximize student admission and student allocation into departments and academic programmes respectively. In the first stage, we seek to determine the optimal number of new student intake in all the departments of a given faculty by observing the departments’ capacity limitations in terms of lecture rooms/halls availability, budget constraints, number of faculty members and affirmative action quota. The second stage concerns the application of the same procedure with the objective of determining the optimal allocation of students obtained in the first stage into the respective academic programmes within the same department with constraints unique to each academic programme. Every constraint has its own weightage besides its level of priority. We then describe the application of the model to the Faculty of Science & Technology of the Universiti Kebangsaan Malaysia with its five academic centres/departments and then to the Centre for Mathematical Sciences with its three academic programmes. For both stages, we compare the results of the preemptive goal programming model with the non preemptive weighted goal programming model to analyse the adaptability of the models to real situations. Sensitivity analyses of the results are done to gauge the reliability of the model. We hope that the results of the application will demonstrate the model’s capability to provide an optimal apportionment of student admission policy with regard to the number of student intake and allocation into the departmental academic programmes of a faculty, as well as recognizing the capacity limitations of each academic programme.